Digital Constitutionalism and Human Rights: The Right to Internet Access from National and Global Perspectives - Atmaja, Bima Kumara Dwi (Universitas Pendidikan Ganesha, 2025)
This study aims to examine the development of digital constitutionalism within the framework of human rights protection, with particular emphasis on the right to internet access from national and global perspectives. The research employs a normative legal method using statutory, conceptual, and comparative approaches. Primary legal materials include international human rights instruments, provisions of the Indonesian Constitution, and relevant judicial decisions concerning internet access restrictions. Secondary materials are drawn from scholarly literature on digital constitutionalism and human rights in the digital era. The findings indicate that although the right to internet access is not explicitly recognized as a constitutional right under the 1945 Constitution of the Republic of Indonesia, its normative foundation can be derived from constitutional guarantees of freedom of expression and the right to information. The case of Anuradha Bhasin v. Union of India demonstrates that state-imposed restrictions on internet access must comply with the principles of legality, proportionality, and necessity. This study concludes that the internet has evolved beyond a mere technological tool into a fundamental prerequisite for the effective exercise of various human rights, thereby requiring states to regulate and protect internet access within a democratic and human rights–based framework of digital constitutionalism.